Stress among Hospitalized Patients at Teaching Hospital, Chitwan - Lama, Sumita; Ghimire, Srijana (Journal of Chitwan Medical College, 2019)
Background: Stress is defined as “the non- specific physiologic response of the body to any demand made upon it. Stress is a state produced by a change in the environment that is perceived as a challenging, threatening or damaging to a person’s dynamic balance or equilibrium. This study tries to find out the stress among the hospitalized patients. Methods: A descriptive, cross sectional study design was used to find out the stress among the hospitalized patients of Chitwan Medical College Teaching Hospital, Chitwan. Purposive sampling technique was used. Structured interview schedule was used to collect the data. The data was edited, coded and analyzed using statistical package of social sciences (SPSS) version 16.0. Descriptive and inferential statistics was used to analyze the data. Results: Out of 84 respondents, 52.4% respondents were female. Findings of the study revealed that more than half of the respondents 57.1% had high stress. So this study showed that the patients had high level of stress during hospitalization. The result also showed that there was statistically significant association between level of stress and sex of the respondents (p=0.002), educational status (p=0.002), place of residence (p=0.01), sufficiency of family income (0.02), previous experience of hospitalization (p=0.03). The major stressors identified in this study were economic stressors, stressors related to family role, disease condition. The minor causing stressors were stressors related to professional behaviors of health personnel and hospital related stressors. Conclusions: Stress reduction activities such as counseling, warm environment should be provided for the patients to enhance the quality of life by reducing stress.